ISU GENDER DALAM PERSPEKTIF AGAMA DAN PERUNDANG-UNDANGAN - HENNY YULIATI (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2023)
Eachreligion teaches that men and women have equal positions and roles so that in life they can walk side by side and complement each other. In the sense that the roles and jobs that men usually do can be done by women, and vice versa. Women's roles and jobs can also be men who do it. The existence of inequality of position and role between men and women in society stems from the wrong perception of